PENGARUH PUPUK ORGANIK DAN FOSFOR (P) TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH LOKAL MUNA (Zea mays l.) PADA TANAH ULTISOL KENDARI - Ansi, Azhar (Jurusan Penyuluhan Pertanian FP UHO, 2026)
The aim of the research was to study the effect of organic fertilizer and phosphorus fertilizer (P)on the growth and yield of peanut on ultisol soils in Kendari. The study was conducted in the Labibia sub district, Kendari city, from January to May 2025. The study was arranged in a randomized block design (RBD) in a factorial pattern with three replications consisting of 2 factors. The first factor was organic fertilizer which consisted of 4 levels, namely: control (B0), 5 t ha-1 (B1), 10 t ha-1 (B2), and 15 t ha-1 (B3). The second factor was P fertilizer which consisted of 3 levels, namely control (P0), 50 kg ha-1 (P1), and 100 kg ha-1 (P2) so that there were 4x3x3=36 experimental units. Observation variables included: plant height, leaf area, weight of 100 seeds, yield per plot and yield per ha. The results showed that there was an interaction between organic fertilizer and combination of P fertilizer on the observed variables. The best results were obtained in the treatment of 15 t ha-1 of organic fertilizer and 100 kg of P fertilizer with the highest production reaching 0,99 t ha-1.